"You Better Say Your Prayers and Get Ready": Guns Within the Context of Partner Abuse. Issue 4 (February 2018) - Lynch, Kellie R.; Logan, TK
The present study used focus groups to collect qualitative data to better understand the complexity of how women with domestic violence experiences feel about gun violence and protections from gun violence within the context of partner violence. Participants consisted of 42 women who were recruited through domestic violence shelters and programs in a single U.S. state. Three main themes were examined in the focus group discussions: (a) guns used within the context of partner abuse, (b) victims using guns as protection from an abuser, and (c) mandated gun restrictions as protection in partner abuse. A total of nine subthemes were organized under the three general themes. Within the first main theme, participants discussed that although abuse occurs with and without guns, guns are uniquely dangerous. In the second main theme, participants expressed concern regarding the dangers of using a gun for self-defense as well as the individual right to own a gun for self-defense. In the third main theme, participants expressed their frustrations that victims are not taken seriously by the justice system and the difficulties of enforcing mandated gun restrictions. The findings have implications for developing protective strategies against gun violence for victims of partner violence.